2021
DOI: 10.21203/rs.3.rs-590616/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Saturated Steam on Moso Bamboo Quasi-static Micromechanical Properties: Nano-Scale Evaluation

Abstract: In this paper, in order to analyze the quasi-static properties of Moso bamboo, a new, environmentally friendly and eco-friendly method was used for bamboo thermal modification under the effect of saturated steam. Under saturated steam heat treatment, the chemical composition in bamboo decreased, and the bamboo cell wall shrunk slightly. The increased crystallinity index of cellulose and decreased intensity of peaks belong to hemicellulose were confirmed by XRD and Fourier transform infrared (FTIR) spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The increased compression resistance appears to be due to the changes in the properties of the matrix that become more brittle with temperature treatment as elucidated by one study [15]. There is also the process of lignification of bamboo fiber as reported in [16] which forms an amorphous network which can enclose the holocellulose and can increase the micromechanical properties of the bamboo. Lastly, one investigation [17] has shown that there are three kinds of fracture behaviors within the bamboo microstructure during the deformation and fracture process which are matrix (parenchyma cells) failure, fiber dissociation and fiber breakage.…”
mentioning
confidence: 93%
“…The increased compression resistance appears to be due to the changes in the properties of the matrix that become more brittle with temperature treatment as elucidated by one study [15]. There is also the process of lignification of bamboo fiber as reported in [16] which forms an amorphous network which can enclose the holocellulose and can increase the micromechanical properties of the bamboo. Lastly, one investigation [17] has shown that there are three kinds of fracture behaviors within the bamboo microstructure during the deformation and fracture process which are matrix (parenchyma cells) failure, fiber dissociation and fiber breakage.…”
mentioning
confidence: 93%